Baker’s Company ( An E-commerce Application) - Vishnu Sharma; Shivani Baliyan; Abhishek Rai; Vaibhav Panwar (E-COMMERCE FOR FUTURE & TRENDS, 2021)
A bakery industry is playing a very important role in the lives of people who likes to eat baked foods like cakes, pastries, cookies etc. The market of bakery industry is categorized as cafes, restaurants that serve coffee, tea and baked food to customers who wish to consume them. As Now a days the technology plays a vital role in our lives to make our life easier. The use of mobiles operating systems like ios and android is becoming very significant now a days. We can use a bakery product delivery application that provides a solution to a large number of consumers and with the help of bakery application we can order the bakery products online and can get it at our doorstep without any efforts. Based upon application of bakery market, there are supermarkets, cafes and online delivery of bakery products with the help of Bakery app. This research paper is about the bakery application we developed to get the bakery items ordered online. The application Baker’s Company helps bakery shops and home bakers to automate bakery selling online. Home Bakers and passionate people can sell their bakery items and products on this application.